Skeletal Fluorosis: “Huffing” of Inhalant Computer Cleaning Fluid - Austin Jasniewski; Udaya M. Kabadi (Annals of Internal Medicine: Clinical Cases)
Skeletal fluorosis is a disorder characterized by the deposition of fluoride within the bones. It is a rare presentation in the United States since the administration of sodium fluoride for the treatment of osteoporosis was discontinued several years ago. We report an adult woman manifesting skeletal fluorosis involving both axial and appendicular bones secondary to “huffing” (inhalation) of various commercial electronic cleaning products containing 1,1 difluoroethane. It is important to be alert to the presence of this disorder in patients abusing inhalants to prevent bone deformities, fragility fractures, and consequential morbidities.